Organized Neurogenic-Niche-Like Pinwheel Structures Discovered in Spinal Cord Tissue-Derived Neurospheres - Rodriguez-Jimenez, Francisco Javier; Clemente, Eleonora; Moreno-Manzano, Victoria; Erceg, Slaven (Frontiers in Cell and Developmental Biology, 2019)
ABSTRACT The neurogenic niche of the subventricular zone (SVZ) in adult brain tissue takes the form of a pinwheel-like cytoarchitectural structure, with mono-ciliated astrocytes displaying neural stem cell (NSC) characteristics present in the core surrounded by ciliated ependymal cells. For the first time, we have demonstrated the formation of similar pinwheel structures in spinal cord tissue-derived neurospheres cultured in vitro. To investigate whether the organization and integrity of these pinwheel structures depends on the appropriate organization of ciliated astrocytes and ependymal cells, we modified neurosphere cell arrangements via the application of the methyltransferase inhibitor 5-aza-2'-deoxycytidine (5-aza-dc) or the antiviral drug ganciclovir (GCV) in GFAP-TK transgenic mice. Treatment of neurospheres with 5-aza-dc increased FoxJ1 expression, a crucial factor for ciliogenesis, by reducing methylation of the FoxJ1 CpG island. 5-aza-dc also increased the expression of the astrocyte marker GFAP by other mechanisms, regardless of Foxj1 expression, and caused aberrant accumulation of ciliated astrocytes. However, the ablation of dividing astrocytes within neurospheres by GCV treatment led to an increase in the accumulation of ciliated ependymal cells as evidenced by the increased expression of the ependymal cell marker Vimentin or CD24. While 5-aza-dc and GCV treatment differentially affected cell arrangement, both compounds significantly diminished the number of pinwheel structures present in neurospheres. Thus, we suggest that the ratio of ciliated astrocytes to ependymal cells plays a crucial role in the correct formation of the pinwheel structures in spinal cord tissue-derived neurospheres in vitro.